Curadoria de planos de aula para o ensino de Língua Portuguesa à luz da pedagogia dos multiletramentos - Carvalho, Naiara Chaves de (2023)
Due to the need of investigating the process of curating Digital Educational Resources of Portuguese Language, by teachers and researchers, under the scope of Applied Linguistics, discussions have been undertaken regarding digital curation in different Higher Education Institutions in Brazil. Linked to this same interest, this research aimed to evaluate, through digital curation, lesson plans on the New School platform that were inclined to work with discursive practices that are related to the elements of design and the four factors of the Multiliteracy Pedagogy (situated practice, explicit instruction, critical framing, and transformed practice). In this study, we questioned whether educational portals, such as New School, currently contribute and favor Portuguese language teachers, access to lesson plans that are aimed at developing the perspective of multiliteracies. In addition, another issue that mobilized this investigation was how the steps of selecting, evaluating, editing, formatting and sharing – pillars of the digital curation process in LA – can be carried out by teachers in the curatorial process of lesson plans. In order to answer the questions of this research, qualitative analyzes were configured based on the methodological assumptions of the descriptive-exploratory research. To compose the corpus of this study, 45 lesson plans were selected from New School. The first goal was to map lesson plans aimed at discursive practices that are aligned with the perspective of multiliteracies, through the applicability of digital curation movements and actions and, subsequently, to analyze, in each plan, possibilities for the attainment of a work that favored the linguistic, cultural and technological multiplicity of discursive practices in contemporary times. With this objective, the evaluation of the plans was carried out using as categories of analysis the four components that make up the Pedagogy of Multiliteracies and the different types of designs. This work was theoretically anchored in the enunciative-discursive perspective of language, in the discussion of digital curation in LA and in the Pedagogy of Multiliteracies. To assist in carrying out the curation process, the movements and actions proposed by Araújo (2019), Silva (2019) and Silva and Araújo (2022) were taken as a parameter. Furthermore, we are based on the considerations of the National Curricular Parameters (PCN) and on the National Common Curricular Base (BNCC) with regard to the curricular component of the Portuguese Language. The results show that, by proposing activities that allow students to use their knowledge and skills to solve real problems in the community and promoting a significant social transformation, the plans curated in this investigation have directions that meet the characteristics of the Multiliteracy Pedagogy, in addition to being organized from the four factors indicated by Pedagogy. The data also indicate that the classes propositions consider language in a dialogic perspective. Although they are aligned with multiliteracies, some lesson plans have some gaps, such as the absence of a critical approach about oral practices and their role in building power and domination relations in the society; some activities are at the edge of the classroom; in some propositions we noticed the lack of a more systematic approach to multimodality; among other gaps. We also verified, with this study, that digital curation can be a useful tool in the selection and evaluation of lesson plans and, in the context of LA, a digital curator can select lesson plans that are aligned with Multiliteracies, with the use of multiple languages and media, valuing students' background knowledge and promoting critical reflection about the use of digital technologies in education.